Images of Mathematics Held by Undergraduate Students - Lamichhane, Basanta Raj; Belbase, Shashidhar (Universitas Ahmad Dahlan, 2017)
The purpose of this study was to explore images of mathematics held by undergraduate students and possible influencing factors. The image of mathematics in this study was conceptualized as the mental representations or views of mathematics as undergraduate students experienced during their academic journey through the interaction largely at school. Pierre Bourdieu's construct of symbolic violence served as the theoretical lens to evaluate the students' images of mathematics. The design of this study was explorative qualitative and interpretive. Semi-structured interview was used to generate data texts from three participants who were senior undergraduate students studying mathematics at an affiliated college of Tribhuvan University in Kathmandu. From the thematic analysis and interpretation of the textual data, four common themes emerged as images of mathematics held by the participants. These themes were mathematics as difficult and abstract, as decontextualized, as mysterious subject, and as applicable in different fields. The influencing factors on the formation of these images were largely related to the curricular and pedagogical approaches from schools to university classes. These are conventional and disempowering methods of teaching, decontextualized curriculum and textbooks and other teaching learning resources, medium of instruction and nature of mathematics itself.